Anonymous Linkage Between College Students and Human Immunodeficiency Virus (HIV) Facilities: Systematic Evaluation of Urine Self-Collection for HIV Testing Initiative in China. (8th December 2020) - Lv, Yi; Li, Guanqiao; Hu, Maogui; Xu, Chengdong; Lu, Hongyan; Chen, Lu; Xing, Yan; Liang, Shu; Ma, Yanling; Liang, Shujia; Zhuang, Minghua; Li, Yi; et al.
Abstract: Background: Identifying young individuals living with human immunodeficiency virus (HIV) who are unaware of their status is a major challenge for HIV control in China. To address this, an innovative, anonymous vending machine–based urine self-collection for HIV testing (USCT) program was implemented in 2016 in colleges across China. Methods: From June 2016 to December 2019, 146 vending machines stocked with urine self-collection kits were distributed on 73 college campuses across 11 provinces of China. Urine samples were collected, delivered, and tested in an anonymous manner. We analyzed the returned rate, reactive rate (likelihood of HIV screening positive), testing effectiveness (the annual number of college students living with HIV screened by USCT or other testing methods), and the spatiotemporal relationship between USCT usage and student activity per college generated from the usage of a social networking application. Results: Among the 5178 kits sold, 3109 (60%) samples were returned; of these, 2933 (94%) were eligible for testing. The HIV reactive rate was 2.3% (66 of 2933). The average effectiveness ratio among the 34 participating Beijing colleges was 0.39 (12:31) between USCT and conventional testing methods. A strong spatiotemporal correlation between USCT numbers and online student activity was observed during school semesters in Beijing. Conclusions: USCT is a powerful complement to current interventions that target at-risk students and promote HIV testing. The social networking–based evaluation framework can be a guide in prioritizing at-risk target populations. Abstract : The world's first vending machine–based, decentralized, anonymous urine self-collection system for human immunodeficiency virus testing was launched in Chinese colleges since 2016. This approach was proven to reach high-risk students by cross-analysis of social networks used by these groups.